2015
DOI: 10.1179/2054892315y.0000000009
|View full text |Cite
|
Sign up to set email alerts
|

Direct analysis in real time-mass spectroscopy for identification of red dye colourants in Paracas Necropolis Textiles

Abstract: The Paracas Necropolis on the south coast of Peru is renowned for the elaborate funerary bundles recovered from that dry sandy region. These bundles contained the remains of male leaders within the Paracas communities surrounded by multiple layers of plain cloth and garments with embroidered designs. The methods and materials used in dyeing the yarns used to embellish these ancient fabrics are still not well understood, and the research presented herein seeks to add to that body of knowledge. To investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Combinations of methods have shed further light on the ornate textiles and other objects from mummy bundles from South America [8]. Mass spectrometry with ambient ionisation [9] has shown that plant dyes from Relbunium species can be identified rapidly in Paracas textiles, confirming results first reported by Saltzman [10]. Burr [11] demonstrated the use of surface enhanced Raman spectroscopy (SERS) to differentiate between the plant and insect red dyes used in ancient Peru using only single fibers.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Combinations of methods have shed further light on the ornate textiles and other objects from mummy bundles from South America [8]. Mass spectrometry with ambient ionisation [9] has shown that plant dyes from Relbunium species can be identified rapidly in Paracas textiles, confirming results first reported by Saltzman [10]. Burr [11] demonstrated the use of surface enhanced Raman spectroscopy (SERS) to differentiate between the plant and insect red dyes used in ancient Peru using only single fibers.…”
Section: Introductionmentioning
confidence: 62%
“…As previously observed, DART-MS does not reliably detect carminic acid and generally only traces of compounds characteristic of cochineal dye are observed by DART-MS directly [9]. More readily ionised minor components from cochineal, primarily kermesic acid, are often observed if the fibers are first treated with a few microliters of 88% formic acid, indicating that these compounds can provide some evidence of the presence of insect dyes.…”
Section: B Dart-msmentioning
confidence: 78%
See 2 more Smart Citations
“…The reported composition suggests that the dye source employed belonged to Relbunium vegetal species. The comparison of the obtained pro les with those of some Relbunium species employed for dyeing alpaca and sheep bres from the Saltzman collection (Relbunium hypocarpium, Relbunium ciliatum, Relbunium-unknown species), already characterized in the literature (13,18) allowed us to conclude that the most plausible vegetal source for the three samples is Relbunium hypocarpium. The small differences in composition could be due to the use of a mixture of different Relbunium species, different dyeing processes or degradation of the textiles.…”
Section: Red Threadsmentioning
confidence: 93%